The ethics of market in the news production of Folha de S. Paulo newspaper - Barros, Antonio Teixeira de (Universidade Estadual Paulista / UNESP, 2007)
Analysis of the production of the news as it appears in the Folha de S. Paulo, with emphasis on the application of the concept of news publishing as applied to the current practices of this newspaper, as well as those of the Projeto Folha. Identification of the principal ways in which news is falsified or manipulated. Adoption of a critical perspective of the news, including those concepts which consider news as information tranformed into merchandise. Pressuposition that basically the concept of news as produced by the FSP, as well as the criterions adopted by the Projeto Folha, constitute, essentially, a marketing strategy allied to the merchandising ethics which are adopted by this newspaper. Utilization of documentary research and content analysis as techniques for collecting data. Utilization of a sampling taken from the FSP, in edition published from the 1st to the 12th of april, 1992. Partial confirmation of principal hypothesis. Identification of principal ways in which news is falsified and/or manipulated: to show off, fragmentation, personalization, politics of distinction and supression of information.